Peran Bimbingan Belajar Sebagai Alternatif Meminimalisasi Penggunaan Gaway Pada Anak Usia SD di Dusun Mening Desa Prajegan Sukorejo Ponorogo - Salis Musthofa; Suci Midsyahri Azizah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to explore the role of tutoring in minimizing gadget use among elementary school-aged children in Prajegan Village through the Participatory Rural Appraisal (PRA) method. With the increasing use of digital technology, children often fall into excessive gadget use, which can interfere with their academic and social development. This study employs a qualitative approach using PRA techniques, including participatory interviews, direct observations, and focus group discussions with parents, tutors, and children. The findings indicate that effective tutoring not only improves children's academic skills but also reduces their dependence on gadgets. Tutoring programs designed using the PRA method enable active participation from all parties to create interactive and educational activities, which can divert children's attention away from gadgets and provide them with more beneficial alternatives. Therefore, tutoring through the PRA method plays a crucial role in supporting children's development by reducing screen time and enhancing their engagement in more productive activities. The results of this study provide important insights for educators and parents in designing strategies to manage screen use and promote more balanced learning in the digital age.